DEVELOPMENT OF AN ACTIVE COOLING SYSTEM FOR PERFORMANCE ENHANCEMENT PHOTOVOLTAIC MODULE WITH THERMAL CHARACTERISTIC ANALYSIS - Agustion Tomayahu, Syafril
Solar energy has great potential to support efforts to reduce carbon emissions and meet electricity needs through renewable energy sources in Indonesia. This research aims to develop an active cooling system for photovoltaic modules with thermal characteristic analysis to improve the efficiency of photovoltaic modules. (PV). Through experiments, the development of this system began with the development of a water distribution system using a microcontroller that automatically regulates the water flow based on the surface temperature of the PV module. This system is integrated with various sensors to monitor temperature, solar irradiation, PV module current, PV module voltage, and flowmeter in real-time, allowing for timely and efficient responses to the operational conditions of the module. Testing was conducted by comparing modules without cooling and with active cooling. The experimental results show a non-linear decrease in efficiency in the module without cooling when the temperature exceeds 45 degrees Celsius. In the module with active cooling, there is an efficiency increase of up to 10.65% through reducing the module temperature to a lower operational limit. The active cooling system, in addition to controlling the temperature, also functions as a cleaning mechanism that reduces dust accumulation, which can lower the performance of the module. Based on the analysis of thermal characteristics, the active cooling system plays a significant role in enhancing the performance efficiency of photovoltaic modules by maintaining operational temperature and preventing efficiency loss due to temperature rise. The temperature coefficient ? of 1.59%/°C indicates that every 1°C increase in the module's operating temperature results in a 1.59% decrease in efficiency. The temperature of the module without cooling reaches 51.1°C with a heat transfer coefficient (hc) of 50.30 W/m².°C, whereas with cooling, the module's temperature is successfully reduced to 35°C with a convective heat transfer coefficient increased to 211.60 W/m².°C. Thus, the active cooling system effectively maintains the module's temperature, enhances heat dissipation, and preserves the efficiency of the photovoltaic module.